AKT-mediated phosphorylation of TSC2 controls stimulus- and tissue-specific mTORC1 signaling and organ growth - Cormerais, Yann; Lapp, Samuel C.; Kalafut, Krystle C.; Cissé, Madi Y.; Shin, Jong; Stefadu, Benjamin; Personnaz, Jean; Schrötter, Sandra; Freed, Jessica; D’Amore, Angelica; Martin, Emma R.; Salussolia, Catherine L.; et al. (Developmental cell, 2025)
Mechanistic target of rapamycin (mTOR) complex 1 (mTORC1) integrates diverse growth signals to regulate cell and tissue growth. How the molecular mechanisms regulating mTORC1 signaling-established through biochemical and cell biological studies-function under physiological states in specific mammalian tissues is undefined. Here, we characterize a genetic mouse model lacking the five phosphorylation sites on the tuberous sclerosis complex 2 (TSC2) protein through which the growth factor-stimulated protein kinase AKT can activate mTORC1 signaling in cell culture models. These phospho-mutant mice (TSC2-5A) are developmentally normal but exhibit reduced body weight and the weight of specific organs, such as the brain and skeletal muscle, associated with cell-intrinsic decreases in growth factor-stimulated mTORC1 signaling. The TSC2-5A mice demonstrate that TSC2 phosphorylation is a primary mechanism of mTORC1 regulation in response to exogenous signals in some, but not all, tissues and provide a genetic tool to study the physiological regulation of mTORC1.